Application of Building Playing in the Center of Beams to improve the Visual-Spatial Intelligence of Children at the Age 5-6 Years Old in Mutiara Insan Kindergarten, Sukoharjo Regency - Utami, Sri Ngadinah Amrih; Adiarti, Wulan (Jurusan PGPAUD FIP UNNES, 2017)
Visual-spatial intelligence is the ability to understand picture and shape including the ability to interpret the invisible space dimension. Visual-spatial intelligence have the characteristics they are the sensitivity toward line, color, shape, space, balance, the ability of imagine, interpreting the idea visually and spatially, so it is rests on the sharpness of seeing and the accuracy of observing. Optimized of visual-spatial intelligence in children at the early childhood development can be done through building games by using beam as the media which have been available in the center of beams. The existence of building play is the media to practice the ability that is needed by the children and also to stimulate the ability of children to create the thoughts, ideas, and concepts. The objective of this study is to know the increase in visual-spatial intelligence which is reached by the children at the age 5-6 years old through the activity playing of building in the center of beams. Experimental research is used in this quantitative research with the design One Group Pretest-Posttest. The populations of this study are all of the students of Mutiara Insan Kindergarten, Sukoharjo Regency with the sample of 30 students consisting of children at the age of 5-6 years old (grade B kindergarten). The sampling technique used was Purposive sampling. Whereas data collection methods of this study using children visual-spatial intelligence scale which have been tested both the validity and the reliability for about 0,901. The data distribution obtained indicates normal data and homogenous. The statistical analysis method with Paired Sample t-Test technique is the result of pretest and posttest. The result obtained tcalculate = -102,524 with sig = 0.000, so that the average score pretest and posttest of the children visual-spatial abilities at the age of 5-6 years old experience significant improvement after conducted optimization of beam as a media for application the building games in the center of the beam.